SOCIO-ECONOMIC CONCERNS, CULTURAL PRACTICES, LIVING CONDITIONS, AND HEALTH-SEEKING BEHAVIORS AMONG THE PRIMITIVE KATTUNAYAKAN TRIBES IN THE NILGIRIS DISTRICT OF TAMIL NADU - AN EXPLORATORY STUDY - YOGANANDHAM, Dr. G. (The journal of contemporary issues in business and government, 2023)
The Kattunayakan tribes, commonly referred to as forest chiefs, are a hunter-gatherer group that lives in forests, practices traditional medicine, and shuns contemporary Indian culture. In Tamil Nadu and Kerala, the landless Kattunayakan tribe is well-known for their foretelling abilities, aluminum vessel sales, pig herding, and work in the public sector. Speaking of Kattunayakan, they are grouped among 44 communities. They depend on honey for trade, food, and healing. They compete with bears and bees, and their dance and singing are historical reflections of their civilization. Few people who rely on honey and forest products have become Christians. Forests and forest products are essential to the Kattunayakan tribe, a traditional hunter-gatherer society in Tamil Nadu's Nilgiris. They are forest lords and practice a powerful religion. They use simple technologies, work as day laborers, watchmen, guides, and fishermen, and their economy is based on the forests. Using ethnographic and descriptive research techniques, the study investigates caste inclusion in the Indian Census, a contentious tool for developing public policy. It uses both quantitative and qualitative approaches and gathers information from secondary sources. This study looks into the effects of socioeconomic factors on cultural traditions, prosperity, and living standards. This point of view elevates the current issue's historical and economic significance, as well as its recognition as a critical need.